Dynamics of Leadership Strategy: A Literature Analysis of the Role of Leaders in Improving Organizational Performance - Kannemeyer, Uthmaan (PT. Alpha Trianguli Australis, 2025)
The role of leaders in organizations has been a major concern in various management and organizational studies. In public sector organizations, the role of leaders is even more complex because they have to deal with bureaucracy, strict regulations, and high public expectations. Thus, understanding leadership strategies is not only about choosing the right leadership style, but also involves a deep understanding of organizational dynamics, individual needs in the organization, and external conditions that influence the decision-making process. This study uses a qualitative approach with a systematic literature review design. The results of this study are: 1) Leadership strategies play a vital role in improving organizational performance; and 2) Facing the challenges of modern organizations, leaders need to develop a flexible, value-based approach that is able to empower team members.